An analysis of open debates among prospective student organizational leaders in vocational higher education - Angkasa Putra; Sarifah Aini (Jurnal Integrasi Sumber Daya Manusia, 2023)
The annual election of the President of Senat Taruna at Jakarta Technical University of Fisheries (JTUF) is a prestigious event. This democratic process, integral to this government-affiliated institution, signifies the selection of top leaders responsible for instigating significant change. This study analyzes the open debate session of the 2021-2022 Senat Taruna presidential candidates at JTUF. Participation in this session is obligatory, a prerequisite for eligibility for election by active JTUF students. Employing a case study approach, this research aims for a deep understanding and conducts a descriptive content analysis within the specific context. The analysis reveals discernible differences in presented narratives, serving as benchmarks for the candidates’ critical abilities, and references for active voters. Notably, student attendance for these sessions remains below 25%.